Co‐occurrence patterns at four spatial scales implicate reproductive processes in shaping community assembly in clovers. (10th October 2021) - Christie, Kyle; Harrison, Susan P.; Friesen, Maren L.; Strauss, Sharon Y.
Abstract: Competition, niche differences and chance all contribute to community assembly; yet, the role of reproductive interactions between species is often less appreciated. Closely related plant species that share floral form, phenology and habitat often interact through pollination. They potentially facilitate pollinator attraction, compete for pollination services and/or exchange pollen. If reproductive processes are important to co‐occurrence, we predicted that fitness costs of heterospecific pollen transfer or pollen limitation should result in lower rates of co‐occurrence among outcrossing congeners. In contrast, selfers, which may be less exposed to heterospecific pollen, and/or less negatively affected by it, should co‐occur more frequently. Flower size is an excellent proxy for mating system in clovers. Using herbarium records and three independent field datasets, we documented co‐occurrence patterns of Trifolium at 1 m 2 –1 km 2 scales in California. Using a randomization procedure to reshuffle matrices of community membership, we generated null hypotheses for the expected composition of large‐ and small‐flowered species in Trifolium communities of different sizes. Across all spatial scales, large‐flowered outcrossers were over‐represented at sites lacking congeners, but under‐represented in communities with multiple congeners. Conversely, small‐flowered selfers often occupied sites with multiple other Trifolium species. Patterns for plant height and leaf size, which are weakly or strongly correlated with flower size, did not explain co‐occurrence patterns as robustly. Regression analysis and model selection corroborated the null model analyses, indicating that the likelihood of co‐occurrence decreased as flower size, and thus reliance on outcrossing, increased. Synthesis . This study suggests that reproductive traits and processes may be significant contributors to community assembly and co‐occurrence in flowering plants. Abstract : Across multiple datasets and spatial scales, the likelihood of Trifolium co‐occurrence decreases as flower size, and thus reliance on outcrossing, increases. These results suggest that reproductive traits and processes may be significant contributors to community assembly and co‐occurrence in flowering plants.